A preliminary analysis of biomechanics and saccadic responses for concussion. (July 2020) - Post, Andrew; Hashim, Eyesha; Ting, Windsor Kwan-Chun; Hoshizaki, T. Blaine; Gilchrist, Michael D.; Cusimano, Michael D.
Background: Concussion is an injury that occurs in non-sporting and sporting environments. To determine improved clinical methods for identifying this injury, it is important to develop and understand how the impact event results in quantifiable differences in brain functioning—functioning that has been quantified in the past using saccadic measures. The purpose of this research was to examine the relationships between oculomotor deficits, specifically antisaccade responses, and the biomechanics of impact for a concussion. Methods: Participants underwent a diffusion tensor imaging protocol as well as saccadic testing to determine differences in brain functioning in comparison to controls. The injury event was then reconstructed in laboratory using physical and finite element models to determine the biomechanics of the impact and brain tissue strain. Relationships between the biomechanical variables and antisaccade responses were then examined. Results: The diffusion tensor imaging analyses found that there was a decrease in radial diffusivity and axial diffusivity found in the cerebral peduncle (p < 0.05) and cingulum hippocampus (p < 0.05), respectively. There was an increase in the axial diffusivity for the corona radiata (p < 0.05). The saccadic testing found an increase in mean latency for the concussed group (p < 0.05). The results indicated no significant relationship between mean latency, duration, amplitude and peak velocity antisaccade measures and the biomechanical variables. This may have been influenced not only by a lack of sensitivity in biomechanical variable to antisaccade responses, but also to these responses being affected by factors other than injury such as attentiveness and wakefulness. Conclusion: While the sample of this research was small, this research suggests that to improve the understanding of the relationship between impact biomechanics and concussion, methods that can quantify the damage to brain structures through imaging, such as diffusion tensor imaging, may be more appropriate.